2021
DOI: 10.4070/kcj.2020.0323
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Thermal Injury after Catheter Ablation for Atrial Fibrillation with High-Power (50 Watts) Radiofrequency Energy

Abstract: Background and Objectives Data regarding the safety of atrial fibrillation (AF) ablation using high-power (50 W) radiofrequency (RF) energy in Asian populations are limited. This study was conducted to evaluate the incidence and pattern of esophageal injury after high-power AF ablation in an Asian cohort. Methods We searched the prospective AF ablation registry to identify patients who underwent AF ablation with 50 W RF energy using the smart touch surround flow cathete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A recent study showed that the incidence of EI, which included erosions and ulcers after ablation, was 1.3% for each type of lesion. 20 EI can range from simple esophageal erosions to the more sinister AEF. EI findings may include gastral erosions (22%), esophageal erythema (21%), gastroparesis (17%), hiatal hernia (16%), reflux esophagitis (12%), thermal esophageal lesion (11%), and suspected Barrett esophagus (5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that the incidence of EI, which included erosions and ulcers after ablation, was 1.3% for each type of lesion. 20 EI can range from simple esophageal erosions to the more sinister AEF. EI findings may include gastral erosions (22%), esophageal erythema (21%), gastroparesis (17%), hiatal hernia (16%), reflux esophagitis (12%), thermal esophageal lesion (11%), and suspected Barrett esophagus (5%).…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal injury during RF ablation is not a rare occurrence. A recent study showed that the incidence of EI, which included erosions and ulcers after ablation was 1.3% for each type of lesion respectively (23). EI can range from simple esophageal erosions to the more sinister atrio-esophageal (AE) fistula.…”
Section: Eti In Rf Ablation: Characteristics and Prevention Strategiesmentioning
confidence: 99%
“…PVI with high power (50 W) short duration was effective and safe with shortened procedure time compared to conventional power PVI 27 . In one recent study, 1.3% of esophageal erythema, 1.3% of esophageal erosion, and 15.7% of gastroparesis were reported after PVI with 50 W for 10 seconds at anterior and 50 W for 6 seconds at posterior wall 28 . Although several studies applied 50W as a high power PVI, it can still be questionable about safety, especially at the posterior wall.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In one recent study, 1.3% of esophageal erythema, 1.3% of esophageal erosion, and 15.7% of gastroparesis were reported after PVI with 50 W for 10 seconds at anterior and 50 W for 6 seconds at posterior wall. 28 Although several studies applied 50W as a high power PVI, it can still be questionable about safety, especially at the posterior wall. Our study demonstrated the comparable efficacy and safety of higher power ablation (40 W at anterior and 30 W at posterior) compared to conventional power ablation (30 W at anterior and 25 W at posterior) using the same targeted AI (450 at anterior and 350 at posterior) in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent article in the Korean Circulation Journal , Do et al 8) evaluated the incidence and characteristics of ETI in 196 patients underwent HPSD ablation (RF energy setting: 50W for 5 seconds or 50W for 10 seconds at anterior and 6 seconds at posterior). Their results showed that only 4 (2.5%) patients had ETI including erythematous erosion or superficial ulcer of the esophagus and 25 (15.7%) patients had gastric hypo-motility.…”
mentioning
confidence: 99%